The burden of presumed tuberculosis in hospitalized children in a resource-limited setting in Papua New Guinea: a prospective observational study - Watch, Villa (Int Health, 2017)
BACKGROUND: In Papua New Guinea, TB is considered to be a major public health problem, but little is known about the prevalence and prognosis of presumed TB in children. METHODS: As part of a prospective hospital-based surveillance on the northern coast of mainland Papua New Guinea, the authors investigated the admission prevalence and case fatality rate associated with presumed TB over a 6-year period (2011–2016). All children admitted who were diagnosed with TB were followed-up until discharge or death. RESULTS: Of 8992 paediatric admissions, 734 patients (8.2%) were diagnosed with presumed TB and there were 825 deaths, with TB accounting for 102 (12.4%). Extrapulmonary TB was the final diagnosis in 384 admissions {prevalence 4.3% [384/8992 (95% CI 3.9–4.7)]} with a case fatality rate of 21.4% [82/384 (95% CI 17.4–25.9)]. TB meningitis, disseminated TB and pericardial TB had high case fatality rates of 29.0% (53/183), 28.9% (11/38) and 25% (4/16), respectively. Severe malnutrition was more common in patients with pulmonary compared with extrapulmonary TB (25.4% vs 15.6%; p<0.01). CONCLUSIONS: Improved community-based case detection strategies, routine BCG vaccinations and other effective forms of TB control need revitalization and sustainability to reduce the high case fatality rates associated with childhood TB in Papua New Guinea.